Photocatalytic degradation of Reactive Red 24 in Aqueous Media by Photo-Fenton Reagent (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Advanced oxidation processes (AOPs) are widely used for the removal of health hazardous organic pollutants from industrial and municipal wastewater. Reactive Red 24, which has a complex molecular structure with azo aromatic groups, is widely used in textile industry. Degradation of Reactive Red 24 by Photo-Fenton regent has been investigated under irradiation of visible light in aqueous solution. The parameters that influence degradation such as concentration of Reactive Red 24, FeSO4, H2O2, light intensity and pH of the experimental solution were studied. The optimum condition for the photocatalytic degradation of dye was established. The degradation of dye in the dilute solution follows the first order kinetics.